2011
DOI: 10.1016/j.ejso.2011.08.126
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after immediate breast reconstruction and skin-sparing mastectomy – A comparison with patients undergoing breast conserving surgery

Abstract: IBR is a highly acceptable form of treatment for women requiring mastectomy. With high rates of patient satisfaction, low associated morbidity, and proven oncological safety, it is an appropriate recommendation for all women requiring mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 48 publications
2
52
0
3
Order By: Relevance
“…In contrast to mastectomy, IBR has been shown to provide better cosmetic outcome and superior quality of life, without compromising oncological safety (2)(3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to mastectomy, IBR has been shown to provide better cosmetic outcome and superior quality of life, without compromising oncological safety (2)(3)(4)(5)(6)(7)(9)(10)(11)(12)(13)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…The cosmetic outcome of IBR is superior to mastectomy (5). Literature has proven good psychosocial outcome and quality of life in patients who underwent IBR (2,4,6,7). A study conducted by Al-Ghazal et al showed that patients who underwent IBR showed less psychological distress than patients who underwent delayed breast reconstruction (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve adequate locoregional control, approximately 40 per cent of patients have a total mastectomy2 3. For these patients, breast reconstruction is proven to improve psychosocial and aesthetic outcomes4. Recent guidelines5 6 recommend that reconstruction should be discussed and offered as an option for the majority of women undergoing mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos foram realizados com mulheres em estádio I e II (He et al, 2012;Parker et al, 2007), entretanto há estudos que consideram as mulheres em estádio I, II, III (Han et al, 2010;Shi et al, 2011) e ainda estádio IV (Heneghan et al, 2011). Há também pesquisadores que não informaram o estádio das pacientes (Veiga et al, 2010).…”
Section: Variáveis Clínicasunclassified